Utilization of Unprocessed Sugarcane Bagasse and Coffee Waste into Soap Products - Rachmaini, Fitri; Abdillah, Rahmad; Gumala, Azhoma; Srangenge, Yoneta (Warta Pengabdian Andalas, 2025)
The increasing by-products from sugarcane and coffee consumption have resulted in a greater volume of sugarcane bagasse and coffee waste with potential environmental impacts. Physically and chemically, coffee and sugarcane waste can be processed into soap products without further processing. This community service activity aimed to provide education and practical skills in utilising coffee and sugarcane waste as raw materials for hand soap production. The activity was conducted at the Baitussalam Mosque in Gadut, Padang City, with 20 participants. The implementation methods included material presentation, demonstrations, and hands-on practice in liquid soap formulation. The soap formula used sugarcane and coffee waste as the main ingredients with additional components including Texapon as a surfactant, EDTA as a chelating agent, salt as a viscosity regulator, warm water, and fragrance. The findings indicated that participants comprehended the potential of utilising sugarcane and coffee waste, allowing them to produce a basic liquid soap product for daily usage. Soap made from sugarcane and coffee waste has the potential to become an organic product with antioxidant and antimicrobial benefits for the skin. This activity aims to increase public awareness of the importance of waste management and promote the development of environmentally friendly, nature-based creative enterprises.